Liquidity and firm value in an emerging market: nonlinearity, political connections and corporate ownership - Chia, Yee Ee; Lim, Kian Ping; Goh, Kim Leng (2020)
This study re-examines the relationship between liquidity and firm value in the emerging stock market of Malaysia, exploring the issues of nonlinearity and moderating variables. Using data for all non-financial firms traded on Bursa Malaysia over the sample period of 2000–2015, the results from the baseline quadratic model suggest stocks must be traded higher than the threshold liquidity level before reaping the benefit of larger firm value. Our key finding of a nonlinear relationship remains robust to alternative liquidity measures and estimation methods, as well as passing a series of endogeneity checks. Using an ideal candidate of lot size reduction for Malaysian stocks in May 2003 as exogenous liquidity shock, we establish the causal effect from liquidity to firm value. Further interaction analyses uncover three important moderating variables in the liquidity-firm value relationship, in which the value impact demands a more liquid market for Malaysian public firms with political connections, higher foreign nominee ownership and higher foreign institutional ownership